Regulatory considerations for Cellular Therapy - Kondo, Andrea Tiemi; Ribeiro, Andreza Alice Feitosa (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2022)
Advanced therapy products can be an alternative treatment for several disease. Manufacturing steps and product release are critical points to avoid unsafe use of products. Quality controls tests, manufacturing practice, safety testing and efficacy trials need to be properly accessed before releasing to patients. Regulatory system for cell therapy products determines guidelines for production, clinical trials and registration, considering risk-benefit ratios. This article aims to discuss main aspects of National Regulatory for advanced therapy products.